N‐(2‐Ethylhexyl)carbazole: A New Fluorophore Highly Suitable as a Monomolecular Liquid Scintillator. Issue 34 (13th July 2016) - Montbarbon, Eva; Sguerra, Fabien; Bertrand, Guillaume H. V.; Magnier, Élodie; Coulon, Romain; Pansu, Robert B.; Hamel, Matthieu
Abstract: The synthesis, photophysical properties, and applications in scintillation counting of N ‐(2‐ethylhexyl)carbazole (EHCz) are reported. This molecule displays all of the required characteristics for an efficient liquid scintillator (emission wavelength, scintillation yield), and can be used without any extra fluorophores. Thus, its scintillation properties are discussed, as well as its fast neutron/gamma discrimination. For the latter application, the material is compared with the traditional liquid scintillator BC‐501 A, and other liquid fluorescent molecules classically used as scintillation solvents, such as xylene, pseudocumene (PC), linear alkylbenzenes (LAB), diisopropylnaphthalene (DIN), 1‐methylnaphthalene (1‐MeNapht), and 4‐isopropylbiphenyl ( i PrBiph). For the first time, an excimeric form of a molecule has been advantageously used in scintillation counting. A moderate discrimination between fast neutrons and gamma rays was observed in bulk EHCz, with an apparent neutron/gamma discrimination potential half of that of BC‐501 A. Abstract : Simple excimeric scintillator : The synthesis of N ‐(2‐ethylhexyl)carbazole and its use as a monomolecular liquid scintillator is reported (see figure). This is believed to be the first time that a molecule in its excimer form has been advantageously used as an efficient liquid scintillator.